San Antonio and Some Continuing Concerns of the Cwme - Duraisingh, Christopher (International review of mission, 1989)
The following is a presentation by Christopher Duraisingh, the Director-designate of the Commission on World Mission and Evangelism (CWME), during the final plenary session of the World Mission Conference in San Antonio. This is Dr Duraisingh's impromptu response to the conference in the light of his perception of the role of CWME in world mission; initial comments of a more personal nature have been omitted here.